Synthesis and Characterization of Cerium Doped Titanium Catalyst for the Degradation of Nitrobenzene Using Visible Light - Padmini Ellappan; Lima Rose Miranda (International Journal of Photoenergy)
Cerium doped catalyst was synthesized using Titanium isopropoxide as the Titanium source. The metal doped nanoparticles semiconductor catalyst was prepared by sol-sol method with the sol of Cerium. The synthesized catalyst samples were characterized by powder X-ray diffraction, BET surface area, thermogravimetric analysis (TGA), scanning electron microscopy (SEM), and UV-vis diffuse reflectance measurements (DRS) and compared with undoped TiO2 catalyst. The photocatalytic activity of the sample was investigated for the decomposition of nitrobenzene (NB) using visible light as the artificial light source. Cerium doped catalyst was found to have better degradation of nitrobenzene owing to its shift in the band gap from UV to visible region as compared to undoped TiO2 catalyst. The operational parameters were optimized with catalyst dosage of 0.1 g L−1, pH of 9, and light intensity of 500 W. The degradation mechanism followed the Langmuir Hinshelwood kinetic model with the rate constant depending nonlinearly on the operational parameters as given by the relationship Kapp (theoretical) = 2.29 * 10−4 * Intensity0.584 * Concentration−0.230 * Dosage0.425 * pH0.336.